A pilot study of conically graded chitosan–gelatin hydrogel/PLGA scaffold with dual‐delivery of TGF‐β1 and BMP‐2 for regeneration of cartilage–bone interface. Issue 7 (11th November 2014) - Han, Fengxuan; Zhou, Fang; Yang, Xiaoling; Zhao, Jin; Zhao, Yunhui; Yuan, Xiaoyan
Abstract: Repair of cartilage–bone interface tissue remains challenging, because it combines different cell types and gradients of composition and properties. To enable simultaneous regeneration of bone, cartilage, and especially their interface, a conically graded scaffold of chitosan–gelatin hydrogel/poly(l ‐lactide‐co‐glycolide) (PLGA) was facilely prepared in the study. The chitosan–gelatin hydrogel containing transforming growth factor β1 (TGF‐β1) was used for chondrogenesis, while the PLGA scaffold loading bone morphogenetic protein‐2 (BMP‐2) for osteogenesis. The conically graded transition from the hydrogel to PLGA scaffold and graded variation in amount of growth factors from TGF‐β1 to BMP‐2 benefited the cartilage–bone interface reconstruction. The graded scaffold exhibited spatio‐temporal delivery of TGF‐β1 and BMP‐2. Preliminary results of in vitro cell culture demonstrated that the hydrogel and PLGA phases could promote bone marrow mesenchymal stem cells toward chondrogenic and osteogenic differentiation, respectively. From the result of the pilot in vivo experiment, it showed that the regenerated hyaline‐like cartilage surface and subchondral bone excellently integrated with the native tissues were found by using the TGF‐β1 and BMP‐2 double‐loaded hydrogel/PLGA graded scaffold via H&E and immunohistochemical stainings of collagen I, collagen II, and osteocalcin at 2 months. The obtained preliminary experiment results showed that the hydrogel/PLGA graded scaffold combining multiphasic composition and spatial dual growth‐factor delivery would be useful for cartilage–bone interface tissue defect repair. © 2014 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 103B: 1344–1353, 2015.